Cu-assisted induced atomic-level bivalent Fe confined on N-doped carbon concave dodecahedrons for acid oxygen reduction electrocatalysis. (6th January 2021) - Luo, Yan; Tang, Zeming; Cao, Guiqiang; Bi, Da; Trudgeon, David P.; Loh, Adeline; Li, Xiaohong; Lai, Qingxue; Liang, Yanyu
Abstract: Atomically dispersed transition metals anchored on N-doped carbon have been successfully developed as promising electrocatalysts for acidic oxygen reduction reaction (ORR). Nonetheless, how to introduce and construct single-atomic active sites is still a big challenge. Herein, a novel concave dodecahedron catalyst of N-doped carbon (FeCuNC) with well confined atomically dispersed bivalent Fe sites was facilely developed via a Cu-assisted induced strategy. The obtained catalyst delivered outstanding ORR performance in 0.5 M H2 SO4 media with a half-wave potential (E1/2 ) of 0.82 V (vs reversible hydrogen electrode, RHE), stemming from the highly active bivalent Fe-Nx sites with sufficient exposure and accessibility guaranteed by the high specific surface area and curved surface. This work provides a simple but efficient metal-assisted induced strategy to tune the configurations of atomically dispersed active sites as well as microscopy structures of carbon matrix to develop promising PGM-free catalysts for proton exchange membrane fuel cell (PEMFC) applications. Graphical abstract: A novel concave dodecahedron catalyst of N-doped carbon with well confined atomically dispersed bivalent Fe sites was facilely developed via Cu-assisted induced strategy. The generated FeCuNC can be served as an effective cathode catalyst for oxygen reduction reaction (ORR), which delivered distinguished ORR electrocatalytic performance in 0.5 M H2 SO4 media with an E1/2 of 0.82 V. Image 1 Highlights: A concave dodecahedron catalyst was developed via a Cu-assisted induced strategy. Atomically dispersed bivalent Fe sites made FeCuNC highly active for acidic ORR. The FeCuNC with an E1/2 of 0.82 V is an efficient ORR catalyst in acid media.